Sentido novo da vida rural: a formação de professoras na Escola Normal Regional D. Joaquim Silvério de Souza (1949-1963) - Leonardo dos Santos Neves (2015)
The objective of this research was to identify and analyze teacher training practices at the Regional Normal School Dom Joaquim Silvério de Souza, located in the district of Conselheiro Mata, countryside of Diamantina, Minas Gerais. The hypothesis examined debates about the theoretical and instrumental renovation in the training of Minas Gerais schoolteachers for rural areas. For this purpose, it was necessary to apprehend educational and instructional strategies used in the professional training process of rural normalists by the school of Conselheiro Mata, highlighting the Teaching, clubs and unions in carrying out the teaching practices. The time frame of this study was the interval between the years 1949, initial date that refers to the organization and structuring of the institution of Conselheiro Mata, and 1963, due to the promulgation of the State Decree No. 6879, of 1963, which modify the curriculum to the normal education. In the methodological aspect, bibliographical studies about the history of rural education and more general studies concerning to the sociological discussions about rural and urban categories were performed. Various documentary sources were consulted: legislation, reports and official documents, newspapers, magazines, books and collections, school diaries, photographs, besides the reports of former normalists of Conselheiro Mata. These sources were found in the archives of Regional Normal School D. Joaquim Silverio de Souza; in the archive of the Center of Documentation and Research Helena Antipoff (CDPHE); in the Library Collection of UFMG School of Economics; in the newspapers collection of Antônio Torres Library; in the bibliographic collections of UFMG and UFVJM; and in private collections.